Real-world outcomes of Defocus Incorporated Multiple Segments lenses on retarding axial elongation in myopic children and adolescents - Chun, Rachel K. M.; Wong, Kryshell Y. Q.; Lam, Carly S. Y.; To, Chi-ho; Liu, Kenneth K. K.; Wong, Yin-zhi; Tang, Wing-chun; Chan, Nicole; Kwok, Dora; Cheung, Max; Yung, David; Lam, Andrew K. C. (Frontiers in Medicine, 2025)
PurposeThis study aimed to examine the effect of Defocus Incorporated Multiple Segments (DIMS) lenses on myopia progression and axial elongation in a clinical population.MethodsA retrospective study was conducted using clinical data from 489 and 156 patients aged 3 to 17 years old who were prescribed DIMS and single vision (SV) lenses, respectively at the Optometry Clinic of The Hong Kong Polytechnic University between July 2018 and August 2019. The study included patients with previous myopia control interventions. The changes in spherical equivalent refraction (SER) and axial length (AL) were measured and normalized to annual changes. The correlation between age at baseline and annual change in AL was also examined.ResultsThe total change in SER and AL after DIMS were −0.94 ± 0.79D and 0.55 ± 0.40 mm, respectively with an average wearing period of 31.98 ± 9.97 months. The normalized annual changes in SER and AL in DIMS wearers were significantly smaller than those in SV wearers (DIMS; SER change vs. AL changes; −0.38 ± 0.32D vs. 0.22 ± 0.16 mm. SV; −0.45 ± 0.41D vs. 0.29 ± 0.20 mm, p < 0.05). Patients with a history of myopia control had greater myopia progression after wearing DIMS lenses. There was a significant negative correlation between age at baseline and annual change in AL (correlation coefficient, r = −0.61, p < 0.001), suggesting that myopia progression was faster in children with a younger age of onset. A small proportion of patients (2.7%) experienced a clinically significant axial shortening (total change in AL:−0.13 ± 0.07 mm) after wearing DIMS lenses more than 2 years.ConclusionThe study demonstrated that DIMS lenses could retard axial elongation, with the effect sustained with increased duration of lens wear. However, patients with previous myopia control experienced greater myopia progression after wearing DIMS lenses. The study also highlighted the potential for axial length shortening in a small proportion of patients after the DIMS lens wear. These findings underscore the importance of adherence to intervention in achieving optimal treatment efficacy. Further research is needed to understand the mechanisms underlying these effects and to optimize the use of optical interventions in myopia control.